Improve the energy efficiency of PV systems by installing a soft switching boost converter with MPPT control - Basim Talib Kadhem; Sumer Sahib Harden; Osama Yaseen Khudair Alatbee; Khalid M. Abdulhassan (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
To improve the energy consumption rate of solar cells and reduce switching loss, a maximum power point tracking (MPPT) control approach is presented to manage the boost converter and achieve soft switching. A method for determining the optimal values of the soft switching boost converter design parameters has been proposed, by determining the ideal values for the inductor, capacitor, and duty cycle of the boost converter with soft switching, this method enables the key matching of the PV system with the DC/DC converter configuration. In addition to presenting an analysis of several MPPT methodologies, the entire design of the PV converter system is also included. This study compares the perturb-and-observe (P&O) method and the incremental conductance (IC) method for maximum power point tracking (MPPT) in the MATLAB/Simulink application. The PV systems with both MPPT algorithms have been simulated beginning with an implemented model of the photovoltaic (PV) array together with the soft switching boost converter and its MPPT control. The simulation results based on irradiance and temperature are then shown. In the end, soft-switching is more efficient than hard-switching, especially when operating at full load.